There are (P)lannings and (p)lannings: toward a grammar of social participation in the production of participatory cartographies (PerCursos, 2025)
In recent decades, participatory cartography has become an increasingly prominent tool in both academic research and public policy, establishing itself as a common practice in territorial diagnosis, planning, and management. This raises a critical question: What forms of participation are actually being enacted? This study aims to compare two distinct mapping approaches: the model embedded in the Brazilian Rural Environmental Registry (Cadastro Ambiental Rural – CAR), a state-led environmental protection policy (Mares, 2015), and Social Cartography, a research methodology rooted in ethnography, particularly within anthropological traditions (Almeida, 2013). Theoretically, the analysis draws on the assumption that cartography functions as a power-knowledge apparatus, often serving the interests of those who govern mapping processes. Following Raffestin’s (1993) conceptual distinction, territorial planning may be driven either by Power (P) imposed by the state or by power (p) emerging from civil society initiatives. From this perspective, it becomes essential to critically examine the implications of diverse models of social participation (Souza, 2003). Based on these theoretical premises, a typological framework was developed to classify participatory territorial planning practices. The findings indicate that the examined approaches reveal distinct modes of participation and control over mapping processes. Furthermore, the proposed classification may serve as a tool for future research aimed at identifying patterns and divergences in participatory cartographic practices.
Keywords: territorial planning; power- knowledge; participation and social cartography